Typy i funkcje elementów metatekstowych w "Speculum Saxonum" Pawła Szczerbica (XVI w.) = Types and functions of metatextual elements in "Speculum Saxonum" by Paweł Szczerbic (16th century) - Jurewicz-Nowak, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article was to demonstrate the types and functions of internal metatext. Due to their structure, the following metatexts have been distinguished: lexical-syntactic (e.g. structures with speaking verbs) and graphic-typographic (parenetic notes, graphic signs), and due to their functions: explanatory and clarifying (definitions, examples, additions, supplements, explanations of meaning, terminological equivalents, sentences with verbs of speaking or an equivalent analytical expression describing speaking), instructive, referring to other articles of law, polite, establishing the logical order of statements and expressing equivalence.
Keywords: metatekst; wzory zachowań językowych; język prawny; wspólnota komunikatywna warunkowana prawnie; "Zwierciadło Saskie"; Szczerbic, Paweł (1552-1609); 16 w.; metatext; patterns of linguistic behaviour; legal language; legally determined communicative community; "Saskie Mirror"; 16th century